Kajian Filsafat Hukum Ketenagakerjaan: Rekonstruksi Nilai Keadilan dan Perlindungan Pekerja Dalam Sistem Hukum Indonesia - Suyanto Suyanto; Selamat Widodo; Agusta Awali Amruloh (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study analyzes the role of legal philosophy in shaping labor law and its implications for worker protection in Indonesia. Using a normative juridical method, the study finds that justice, legal certainty, and utility are not yet balanced. A progressive legal approach is required to ensure optimal worker protection.